2020
DOI: 10.1088/1361-6668/ab794b
|View full text |Cite|
|
Sign up to set email alerts
|

Superconductors and Lenz’s law

Abstract: A superconductor has the unique properties of zero resistance and Meissner effect. Lenz's law is a fundamental law of physics. People have occasionally brought up the question that if a superconductor abides by Lenz's law. There has been lack of an explicit answer to this question so far. Recently, we carried out experiments with superconductor coils and a magnet in search of an answer to this question. We find out that the interacting behavior between a superconducting coil and a magnet does not comply with o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 20 publications
(20 reference statements)
2
9
0
Order By: Relevance
“…In the whole energy cycle, the energy can be converted directly from mechanical to electromagnetic then to mechanical without any intermediate equipment, such as motor, generator, and power electronics convertor. Based on the previous studies [6,44], the schematic curve of the force on permanent magnet versus the displacement of permanent magnet is sketched in figure 9. In the figure, the shadow areas visually depict the mechanical energy input/output through the force on the permanent magnet during the energy cycle.…”
Section: New Superconducting Energy Storage Technologymentioning
confidence: 99%
“…In the whole energy cycle, the energy can be converted directly from mechanical to electromagnetic then to mechanical without any intermediate equipment, such as motor, generator, and power electronics convertor. Based on the previous studies [6,44], the schematic curve of the force on permanent magnet versus the displacement of permanent magnet is sketched in figure 9. In the figure, the shadow areas visually depict the mechanical energy input/output through the force on the permanent magnet during the energy cycle.…”
Section: New Superconducting Energy Storage Technologymentioning
confidence: 99%
“…The specific working process of the HTS energy converter is introduced in [8] in detail. From the perspective of energy, the whole process is divided into two stages, including the PM moving from its initial position, i.e.…”
Section: The Hts Energy Convertermentioning
confidence: 99%
“…energization of the superconducting devices rather than transfer the energy out of the superconducting devices. Recently, Ying Xin et al found that a permanent magnet (PM) could not only induce but also exploit the persistent current in a closed HTS ring, realizing the conversion of mechanical energyelectromagnetic energy-mechanical energy wirelessly [8]. In this way, the efficiency in energy conversion is enhanced significantly and current leads are avoided.…”
Section: Introductionmentioning
confidence: 99%
“…Without the SC rings, the magnetic flux produced by the SC coil will enter the iron core, resulting in a significant inductance, which may affect the operation. If the SC rings are installed, induced currents will be generated in the SC rings in the direction to cancel the magnetic flux produced by the SC coil (Lenz's Law) [28]. Thanks to their zero resistance, the flux cancellation could be completed.…”
Section: The Structurementioning
confidence: 99%
“…As the inductance of the SC coil contributes the major part of the impedance of the SFCL in the current limiting process [20,28], the inductance of the SC coil can be approximately considered as the impedance of the SFCL. Therefore, the voltage measured across the SFCL can be approximately regarded as the voltage across the SC coil.…”
Section: The Experimentsmentioning
confidence: 99%